The private rented sector in a new century : revival or false dawn? / edited by Stuart Lowe and David Hughes. - Lowe, Stuart, 1950-; Hughes, David, 1945- (Policy Press, 2002)
Against a century-long trend of decline, the private rented sector grew significantly during the 1990s. This book explores why and looks at the consequences for tenants and landlords, as well as the wider implications for housing policy.